A comparative study of femoral artery and combined femoral and axillary artery cannulation in veno-arterial extracorporeal membrane oxygenation patients - Jin, Na; Pang, Xin; Song, Shiyang; Zheng, Jin; Liu, Zhimeng; Gu, Tianxiang; Yu, Yang (Frontiers in Cardiovascular Medicine, 2024)
Objective Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a critical support technique for cardiac surgery patients. This study compares the outcomes of femoral artery cannulation vs. combined femoral and axillary artery cannulation in post-cardiotomy VA-ECMO patients. This study aimed to compare the clinical outcomes of critically ill patients post-cardiac surgery under VA-ECMO support using different cannulation strategies. Specifically, the focus was on the impact of femoral artery (FA) cannulation vs. combined femoral artery and axillary artery (FA+AA) cannulation on patient outcomes. Methods Through a retrospective analysis, we compared 51 adult patients who underwent cardiac surgery and received VA-ECMO support based on the cannulation strategy employed—FA cannulation in 27 cases vs. FA+AA cannulation in 24 cases. Results The FA+AA group showed significant advantages over the FA group in terms of the incidence of chronic renal failure (CRF) (37.50% vs. 14.81%, p = 0.045), preoperative blood filtration requirement (37.50% vs. 11.11%, p = 0.016), decreased platelet count (82.67 ± 44.95 vs. 147.33 ± 108.79, p = 0.014), and elevated creatinine (Cr) levels (151.80 ± 60.73 vs. 110.26 ± 57.99, p = 0.041), although the two groups had similar 30-day mortality rates (FA group 40.74%, FA+AA group 33.33%). These findings underscore that a combined approach may offer more effective hemodynamic support and better clinical outcomes when selecting an ECMO cannulation strategy. Conclusion Despite the FA+AA group patients presenting with more preoperative risk factors, this group has exhibited lower rates of complications and faster recovery during ECMO treatment. While there has been no significant difference in 30-day mortality rates between the two cannulation strategies, the FA+AA approach may be more effective in reducing complications and improving limb ischemia. These findings highlight the importance of individualized treatment strategies and meticulous monitoring in managing post-cardiac surgery ECMO patients.